Double-zone type synthesis method of high-quality black phosphorus / carbon composite material

By placing red phosphorus and carbon materials in the quartz tubes in partitions and performing dual-zone synthesis using mineralizers and temperature control procedures, the problems of uneven composite and poor crystallinity of black phosphorus/carbon composites are solved, and high-quality and high-efficiency preparation is achieved.

CN120081373APending Publication Date: 2025-06-03YUNNAN YUNTIANHUA
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510260283.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-06
Publication Date
2025-06-03

AI Technical Summary

Technical Problem

In the prior art, black phosphorus/carbon composite materials have problems such as uneven composite, poor crystallinity and low production efficiency.

Method used

The two-zone synthesis method is adopted to partition the red phosphorus and carbon material through a heterotyped two-zone quartz tube, and the uniform composite and crystallization of red phosphorus and carbon material are promoted by mineralizers and temperature control procedures, achieving high-quality preparation of black phosphorus/carbon composite materials.

Benefits of technology

The uniform composite and high crystallinity of black phosphorus/carbon composite materials are achieved, the quality and production efficiency of products are improved, and it is suitable for the preparation of black phosphorus/carbon composite materials with different structures.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120081373A_ABST
    Figure CN120081373A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of battery raw materials, and discloses a double-zone synthesis method of a high-quality black phosphorus / carbon composite material, which comprises the following steps: 1) mixing red phosphorus and a carbon material, and placing the mixture in a closed and vacuum quartz tube; 2) carrying out secondary annealing treatment on the quartz tube; (3) carrying out ball milling treatment; 4) preparing a special-shaped double-zone quartz tube; 5) placing red phosphorus and a mineralizing agent at the raw material end of the special-shaped double-zone quartz tube; (6) vacuumizing and sealing the special-shaped double-zone quartz tube, and then carrying out heat treatment on the special-shaped double-zone quartz tube; 7) taking out the naturally cooled black phosphorus / carbon composite material in a vacuum environment, washing, filtering and drying; the uniform red phosphorus layer loaded on the surface of the carbon material can be converted into black phosphorus, the good crystallinity and lamellar structure of the black phosphorus material can be ensured, and composite materials of different specifications can be obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of battery raw materials, and in particular to a two-zone synthesis method for a high-quality black phosphorus / carbon composite material. Background Art

[0002] Lithium-ion batteries have the advantages of high energy density, no memory effect, and good cycle performance, and show broad application prospects in the field of large-scale energy storage. As one of the key materials of lithium-ion batteries, the anode material plays a crucial role in the performance of lithium-ion batteries.

[0003] Among many anode materials, black phosphorus exhibits the characteristics of high electronic conductivity, high theoretical specific capacity, and high safety. However, at the same time, black phosphorus anodes have problems such as low initial Coulomb efficiency and poor cycle stability, and usually need to be compounded with carbon materials to overcome the above situations. In the prior art, the compounding of black phosphorus and carbon materials is mostly achieved by ball milling or doping methods. The P-C bonds formed in the composite material effectively improve the stability of black phosphorus and improve the volume expansion of black phosphorus during battery cycling. However, the preparation technology of the above black phosphorus / carbon composite material still has problems such as uneven compounding and poor crystallinity of the finished product. At the same time, different structural requirements for the black phosphorus / carbon composite material are required during use, and it is difficult to complete the preparation at one time, resulting in low production efficiency. Summary of the Invention

[0004] The purpose of the present invention is to provide a two-zone synthesis method for a high-quality black phosphorus / carbon composite material to solve the problems of uneven compounding, poor crystallinity, and single product existing in the prior art.

[0005] The solution of the present invention is as follows:

[0006] A two-zone synthesis method for a high-quality black phosphorus / carbon composite material, comprising the following steps:

[0007] 1) Mix red phosphorus and carbon material and place them in a sealed and vacuum quartz round tube;

[0008] 2) Perform secondary annealing treatment on the quartz round tube, and the temperature control program of the secondary annealing treatment is successively heating, cooling, heat preservation, heating, secondary cooling, and natural cooling;

[0009] 3) Take out the red phosphorus / carbon composite material in the quartz tube and perform ball milling treatment on it;

[0010] 4) Prepare a special-shaped two-zone quartz tube. The two ends of the special-shaped two-zone quartz tube are respectively a raw material end and a growth end. The growth end includes a growth zone A and a growth zone B. The length of the growth zone A > the length of the growth zone B, and the inner diameter of the growth zone A > the inner diameter of the growth zone B;

[0011] 5) Place red phosphorus and a mineralizer at the raw material end of the special-shaped double-zone quartz tube; place the red phosphorus / carbon composite material after ball milling in step 3) in growth zone A and growth zone B respectively;

[0012] 6) Seal and evacuate the special-shaped double-zone quartz tube, and conduct heat treatment. The temperature control program for the heat treatment is successively heating, slow cooling, and natural cooling;

[0013] 7) Take out the naturally cooled black phosphorus / carbon composite material successively in a vacuum environment, wash, filter, and dry to obtain the finished product.

[0014] As a preferred technical solution, in step 1), the mass ratio of red phosphorus to the carbon material is 0.2 - 50:1; the carbon material is one or more of graphite, activated carbon, porous carbon, carbon nanotubes, carbon fibers, and hard carbon; the carbon material is a carbon material powder with a mesh size of more than 500.

[0015] As a preferred technical solution, the temperature control program for the secondary annealing treatment is that at room temperature, it is heated to 400 - 500 °C in 1 - 3 h, and the heating rate is 100 - 300 °C / h; it is cooled to 350 - 450 °C in 5 - 10 h, and the cooling rate is 5 -

[0016] 15 °C / h, and keep warm for 2 - 6 h after the cooling ends; then it is heated to 480 - 510 °C in 0.5 - 1 h for the second time, and the second heating rate is 50 - 100 °C / h; then it is cooled to 150 - 200 °C in 2 - 8 h for the second time, and the second cooling rate is 50 - 100 °C / h.

[0017] As a preferred technical solution, in step 3), the rotation speed of the ball milling treatment is 200 - 500 rpm, and the ball milling treatment time is 1 - 3 h.

[0018] As a preferred technical solution, the length ratio of growth zone A to growth zone B is 2 - 10:1; the inner diameter ratio of growth zone A to growth zone B is 2 - 5:1.

[0019] As a preferred technical solution, the mineralizer includes SbI 3 、SnI 4 、SnI 2 or one or more of them.

[0020] As a preferred technical solution, the mass ratio of red phosphorus, the mineralizer, and the red phosphorus / carbon composite material in the special-shaped double-zone quartz tube is 1 - 3:2 - 6:1 - 20.

[0021] As a preferred technical solution, the mass ratio of the red phosphorus / carbon composite material placed in growth zone A to that placed in growth zone B is 1 - 5:1.

[0022] As a preferred technical solution, in step 6), the temperature control program for heat treatment is as follows: under room temperature conditions, the temperature is raised to 500 - 600 °C over 2 - 5 h, with a heating rate of 150 - 350 °C / h; then it is cooled to 200 - 250 °C over 7 - 10 h, with a cooling rate of 20 - 60 °C / h.

[0023] Advantages of the present invention:

[0024] 1) The present invention uses secondary annealing to pre-treat red phosphorus and carbon materials. During the first annealing process, the temperature change is controlled within a small range, enabling the formation of abundant P - C bonds on the surface of red phosphorus and carbon materials, creating good conditions for the uniform composite of red phosphorus / carbon materials during the subsequent secondary annealing process.

[0025] 2) In the present invention, in the presence of a mineralizer, through slow cooling, the uniformly loaded red phosphorus layer on the surface of carbon materials can be transformed into black phosphorus, ensuring good crystallinity and lamellar structure of the black phosphorus materials.

[0026] 3) The designed double - growth - zone special - shaped double - zone quartz tube of the present invention can divide the phosphorus concentration into two gradients. The phosphorus vapor and mineralizer seeds supplemented from the raw material end preferentially condense in growth zone A to form a massive composite material with interpenetrating black phosphorus / carbon lamellae; while the remaining low - concentration phosphorus vapor and mineralizer seeds condense in growth zone B to form a black phosphorus / carbon powder composite material with smaller sizes. Two different - structured black phosphorus / carbon composite materials are prepared at one time, expanding the scope of application of black phosphorus / carbon composite materials and improving production efficiency. Description of the Drawings

[0027] Figure 1 It is a schematic structural diagram of the special - shaped double - zone quartz tube in the embodiment of the present invention;

[0028] Figure 2 It is an SEM image of the massive black phosphorus / graphite composite material grown in growth zone A in Example 1;

[0029] Figure 3 It is an SEM image of the massive black phosphorus / porous carbon composite material grown in growth zone A in Example 3;

[0030] Figure 4 It is an SEM image of the black phosphorus / porous carbon composite material grown in growth zone B in Example 3.

[0031] Among them, 1 - special - shaped double - zone quartz tube; 2 - raw material end; 3 - growth zone A; 4 - growth zone B. Detailed Embodiments

[0032] In order to make the technical means, creative features, achieved purposes and effects of the present invention easy to understand, the present invention will be further described below in conjunction with specific embodiments.

[0033] Figure 1 It is shown that the special-shaped double-zone quartz tube is formed by connecting two sections of round tubes, with the two ends being the raw material end and the growth end respectively. The growth end includes growth zone A and growth zone B, and the length ratio of growth zone A to growth zone B is 2-10:1; the inner diameter ratio of growth zone A to growth zone B is 2-5:1. The length of growth zone A is the distance from the raw material end to the position where the material is placed in growth zone A, and the length of growth zone B is the distance between the position where the material is placed in growth zone A and the position where the material is placed in growth zone B.

[0034] Example 1

[0035] 1) Take 10 mg of red phosphorus and 5 mg of graphite powder, mix them and place them in a sealed vacuum quartz round tube. The quartz round tube is a conventional cylindrical quartz tube.

[0036] 2) Perform a secondary annealing treatment on the above quartz round tube. The temperature control program: first heat from room temperature to 425 °C in 1.5 h, with a heating rate of 267 °C / h, then cool to 400 °C in 5 h, then keep warm at 400 °C for 6 h, with a cooling rate of 5 °C / h; then heat from 400 °C to 500 °C in 1 h for the second time, with a heating rate of 100 °C / h; subsequently, cool to 180 °C in 6 h for the second time, with a cooling rate of 53 °C / h, and naturally cool to obtain the red phosphorus / graphite composite material.

[0037] 3) Take out the red phosphorus / carbon composite material in the quartz round tube and ball mill it at a speed of 200 rpm for 3 h.

[0038] 4) Place 10 mg of red phosphorus and 18 mg of SnI 4 at the raw material end of the special-shaped double-zone quartz tube, place 10 mg of the red phosphorus / graphite composite material in growth zone A with an inner diameter of 20 mm, and place 5 mg of the red phosphorus / graphite composite material in growth zone B with an inner diameter of 8 mm; the length of growth zone A is 10 cm; the length of growth zone B is 5 cm.

[0039] 5) After vacuum-sealing the above special-shaped double-zone quartz tube, perform a heat treatment. The temperature control program: heat from room temperature to 500 °C in 2 h, with a heating rate of 237 °C / h; then cool to 250 °C in 10 h, with a cooling rate of 25 °C / h.

[0040] 6) Take out the black phosphorus / graphite composite material in a vacuum environment, wash, filter, and dry it.

[0041] Figure 2 Figure is the SEM image of the black phosphorus / graphite composite material obtained in Example 1, and it can be observed that black phosphorus and graphite are in an interpenetrating layered composite structure.

[0042] Example 2

[0043] 1) Take 2 g of red phosphorus and 2.8 g of carbon nanotubes, mix them and place them in a sealed vacuum quartz round tube.

[0044] 2) Conduct a secondary annealing treatment on the above quartz tube. Temperature control program: First, heat from room temperature to 485 °C at a heating rate of 184 °C / h over 2.5 h; then cool to 430 °C over 5 h, then hold at the current temperature for 2.5 h with a cooling rate of 11 °C / h; then heat from 430 °C to 510 °C over 1 h with a heating rate of 80 °C / h; subsequently, cool to 200 °C over 3.5 h for the second time with a cooling rate of 88 °C / h, and obtain the red phosphorus / carbon nanotube composite by natural cooling.

[0045] 3) Take out the red phosphorus / carbon nanotube composite in the quartz round tube and ball mill it at a rotation speed of 350 rpm for 1 h.

[0046] 4) Place 1 g of red phosphorus and 1.6 g of SnI 2 at the raw material end of the special-shaped double-zone quartz tube, place 2.8 g of the red phosphorus / carbon nanotube composite in growth zone A with an inner diameter of 3 m, and place 2 g of the red phosphorus / carbon composite in growth zone B with an inner diameter of 10 mm; the length of growth zone A is 15 cm, and the length of growth zone B is 3 cm.

[0047] 5) After vacuum-sealing the above special-shaped double-zone quartz tube, conduct a heat treatment. Temperature control program: Heat from room temperature to 550 °C over 2.5 h at a heating rate of 210 °C / h; then cool to 240 °C / h over 6 h with a cooling rate of 51 °C / h.

[0048] 6) Take out the black phosphorus / carbon nanotube composite in a vacuum environment, wash, filter, and dry it.

[0049] Example 3

[0050] 1) Take 20 mg of red phosphorus and 20 mg of porous carbon, mix them and place them in a sealed vacuum quartz round tube.

[0051] 2) Conduct a secondary annealing treatment on the above quartz tube. Temperature control program: First, heat from room temperature to 450 °C at a heating rate of 212 °C / h over 2 h; then cool to 400 °C over 6 h with a cooling rate of 8 °C / h; then heat from 400 °C to 500 °C over 1 h with a heating rate of 100 °C / h; subsequently, cool to 180 °C over 6 h for the second time with a cooling rate of 53 °C / h.

[0052] 3) Take out the red phosphorus / porous carbon composite in the quartz tube and ball mill it at a rotation speed of 220 rpm for 2 h.

[0053] 4) Place 20 mg of red phosphorus and 18 mg of SnI 4Place it at the raw material end of the special-shaped double-zone quartz tube. Place 30 mg of the red phosphorus / porous carbon composite in growth zone A with an inner diameter of 10 mm, and place 10 mg of the red phosphorus / porous carbon composite in growth zone B with an inner diameter of 5 mm. The length of growth zone A is 10 cm, and the length of growth zone B is 1 cm.

[0054] 5) Heat-treat the above special-shaped double-zone quartz tube. The temperature control program: heat up from room temperature to 600 °C in 3 h, with a heating rate of 191 °C / h; then cool down to 200 °C in 8 h, with a cooling rate of 50 °C / h.

[0055] 6) Take out the black phosphorus / porous carbon composite in a vacuum environment, wash, filter, and dry it.

[0056] Figure 3 It is the SEM image of the black phosphorus / porous carbon obtained in growth zone A in Example 3. It can be observed that the particle size of the composite is about 1 - 5 μm. The layered structure from black phosphorus can be seen on the surface of the composite material, and some porous carbon particles are connected together by black phosphorus. Figure 4 It is the SEM image of the black phosphorus / porous carbon obtained in growth zone B. It can be observed that the particle size of the composite is about 1 - 3 μm, and the average size is significantly Figure 3 smaller. The composite material does not have an obvious layered structure, and its morphology can basically be consistent with the original carbon material.

[0057] The above shows and describes the basic principles, main features and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited by the above embodiments. What is described in the above embodiments and the specification only illustrates the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention will have various changes and improvements, and these changes and improvements all fall within the scope of the present invention claimed. The scope of protection of the present invention is defined by the appended claims and their equivalents.

Claims

1. A dual-zone synthesis method for high-quality black phosphorus / carbon composite materials, characterized in that: The following steps are involved: 1) Mix red phosphorus and carbon material and place them in a sealed and vacuum quartz tube; 2) subjecting the quartz tube to a secondary annealing treatment, wherein the temperature control procedures of the secondary annealing treatment are heating, cooling, heat preservation, secondary heating, secondary cooling and natural cooling; 3) taking out the red phosphorus / carbon composite material from the quartz tube and subjecting it to ball milling treatment; 4) preparing a special-shaped double-zone quartz tube, wherein the two ends of the special-shaped double-zone quartz tube are respectively a raw material end and a growth end, the growth end includes a growth zone A and a growth zone B, the length of the growth zone A is greater than the length of the growth zone B, and the inner diameter of the growth zone A is greater than the inner diameter of the growth zone B; 5) placing red phosphorus and a mineralizer at the raw material end of the special-shaped dual-zone quartz tube; placing the red phosphorus / carbon composite material after ball milling in step 3) in the growth zone A and the growth zone B respectively; 6) The special-shaped dual-zone quartz tube is sealed and evacuated to perform heat treatment, wherein the temperature control procedures of the heat treatment are heating, slow cooling and natural cooling in sequence; 7) Taking out the naturally cooled black phosphorus / carbon composite materials in turn under a vacuum environment, washing, filtering and drying to obtain a finished product.

2. A dual-zone synthesis method for a high-quality black phosphorus / carbon composite material as claimed in claim 1, characterized in that: 1) In the step, the mass ratio of red phosphorus to carbon material is 0.2-50:1; the carbon material is one or more of graphite, activated carbon, porous carbon, carbon nanotubes, carbon fiber, and hard carbon; the carbon material is a carbon material powder with a mesh size of 500 or more.

3. The dual-zone synthesis method of a high-quality black phosphorus / carbon composite material according to claim 1, characterized in that: The temperature control program of the secondary annealing treatment is as follows: at room temperature, the temperature is increased to 400-500°C within 1-3 hours, and the heating rate is 100-300°C / h; the temperature is reduced to 350-450°C within 5-10 hours, and the cooling rate is 5-15°C / h, and the temperature is kept for 2-6 hours after the cooling is completed; the temperature is increased to 480-510°C for a second time within 0.5-1 hour, and the heating rate is 50-100°C / h; the temperature is reduced to 150-200°C for a second time within 2-8 hours, and the cooling rate is 50-100°C / h.

4. The dual-zone synthesis method of a high-quality black phosphorus / carbon composite material according to claim 1, characterized in that: 3) In the step, the rotation speed of the ball milling treatment is 200 to 500 rpm, and the ball milling treatment time is 1 to 3 hours.

5. The dual-zone synthesis method of a high-quality black phosphorus / carbon composite material according to claim 1, characterized in that: The length ratio of the growth zone A to the growth zone B is 2 to 10:1; the inner diameter ratio of the growth zone A to the growth zone B is 2 to 5:

1.

6. The dual-zone synthesis method of a high-quality black phosphorus / carbon composite material according to claim 1, characterized in that: The mineralizer includes one or more of SbI3, SnI4, and SnI2.

7. The dual-zone synthesis method of a high-quality black phosphorus / carbon composite material according to claim 1, characterized in that: The mass ratio of red phosphorus, mineralizer and red phosphorus / carbon composite material in the special-shaped double-zone quartz tube is 1-3:2-6:1-20.

8. The dual-zone synthesis method of a high-quality black phosphorus / carbon composite material according to claim 1, characterized in that: The mass ratio of the red phosphorus / carbon composite material placed in the growth zone A to the growth zone B is 1-5:

1.

9. The dual-zone synthesis method of a high-quality black phosphorus / carbon composite material according to claim 1, characterized in that: 6) The temperature control program of the heat treatment in step 6 is as follows: at room temperature, the temperature is increased to 500-600°C over 2-5 hours at a heating rate of 150-350°C / h; the temperature is decreased to 200-250°C over 7-10 hours at a cooling rate of 20-60°C / h.